What if Surgeons Could Practice Anywhere? - Cota Neto, Amadeo Tato; Teixeira, João Marcelo; Moizes, João Barbosa; Teichrieb, Veronica (Anais do Simpósio de Realidade Virtual e Aumentada (SVR); 2024: Anais do XXVI Simpósio de Realidade Virtual e Aumentada, 2024)
Surgical students must practice procedures in a controlled and safe to make mistakes environment before they perform these procedures on patients. Despite that, surgical practices in these conditions are traditionally limited by the tutor's time availability to provide feedback and by the usage of consumable materials to simulate surgery in a patient. In this context, we developed the "Hand Guide", a virtual reality application that allows expert surgeons to record their hand movements during a simulated surgical procedure and offer it to a surgical student to try to replicate it. The application provides real-time feedback and also a final score at the end of the recorded procedure. Validation with a specialist revealed that the application may be used to teach theoretical content to students with no surgical background and to demonstrate new techniques to experienced surgeons.